Environmental determinants of destination competitiveness and its Tourism Attractions-Basics-Context, A-B-C, indicators: A review, conceptual model and propositions - Lalita A. Manrai; Ajay K. Manrai; Stefanie Friedeborn (Journal of Economics, Finance and Administrative Science, 2020)
Purpose - The purpose of this paper is to provide a comprehensive review of the literature and develop a model of the determinants, indicators and effects of destination competitiveness (DC), as well as several propositions. Design/methodology/approach - This study thoroughly reviewed extant literature to develop a conceptual model and propositions. Findings - Two key findings are listed below. First, 12 different environmental factors are identified and 12 propositions are developed linking these environmental factors to DC. Second, a new indicator of DC is developed, namely, Tourism Attractions-Basics-Context (TABC) model. The TABC model is simple and directly taps into the benefits tourists seek in a destination. Research limitations/implications - Directions for future research are discussed in detail in the paper. Practical implications Managerial implications are discussed in detail in the paper. Originality/value - The extant research on the topic of DC has been rather fragmente
Keywords: 330; Destination competitiveness; Environmental determinants; Tourism ABC (Attractions-Basics-Context) indicators; Tourism performance